FAKTOR-FAKTOR YANG MEMENGARUHI PROFITABILITAS - Effendy, Angela; Dewi, Sofia Prima (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
This study aims to obtain empirical evidence regarding the effect of liquidity, leverage, and company size on profitability. The subjects in this study were manufacturing companies in the primary consumer goods sector that were consistently listed on the Indonesia Stock Exchange for 4 years, namely the 2019-2022 period. This study used 29 manufacturing companies in the primary consumer goods sector which had been selected through a purposive sampling method with a total of 116 data for four years. The data processing technique uses multiple regression analysis which is processed using the Eviews version 12 program. The results of this study indicate that liquidity and firm size do not have a positive effect on profitability, and leverage has a negative effect on profitability.